Quality Assessment of the Spring of Water Ribeirão of Anhumas (araraquara-sp) Through Study of Aquatic Macroinvertebrates - Saulino, Hugo Henrique Lanzi (2011)
In the last decades, anthropic activities such as agriculture activities, industrial and urban effluents and urban areas have been pointed as the main responsible for the alteration and degradation of the aquatic ecosystems. One way of analyzing the water quality of these environments is to study the aquatic microinvertebrated fauna. The present study aimed at analyzing the environmental water quality of Anhumas Stream in the city of Araraquara, SP, Brazil, by studying its aquatic macroinvertebrate community. Two samplings were carried out, being one in February and the other in October, 2008. Three sections of the stream were chosen for study, and two samples were collected at each site totalizing 12 samples. 35 families of macroinvertebrates were collected, totalizing 644 individuals. The Chironomidae family was the dominant one with approximately 57% of the total of collected organisms. The metrics of environmental evaluation using stream macroinvertebrates pointed to the conservation of the Anhumas stream, considering that we found a higher richness of families and a higher percentage of Ephemeroptera, Plecoptera and Tricoptera (EPT) than the ones found in streams with similar environments characteristics near to Araraquara region. The results pointed to the importance of conserving this area as a reference for water´s quality in the region of Araraquara.